Integrated soil moisture fusion for enhanced agricultural drought monitoring in China - Aifeng Lv; Xianglei Yang; Wenxiang Zhang; Yan Han (Agricultural Water Management)
Frequent drought events have a profound impact on the natural environment and socio-economics. Therefore, accurate drought monitoring is essential to prevent and minimize drought losses. In this study, we developed an improved soil moisture dataset (Merged-SM) by using Triple Collocation (TC) and Linear Weight Fusion (LWF) methods to fuse soil moisture data from ERA5-Land, ESA CCI, and MERRA-2. The dataset was validated against in-situ data and applied to investigate the spatiotemporal dynamics of agricultural droughts across China. Results show that (1) Merged-SM exhibits superior accuracy and spatial coverage in comparison to individual datasets, achieving a higher correlation with in-situ data (R = 0.573) and a reduced unbiased root mean square error (ubRMSE = 0.027–0.047). (2) The Merged-SM accurately identified the onset, duration, and spatial extent of agricultural drought events, showing a significant negative correlation with agricultural disaster area (R = −0.418, P = 0.006). (3) Temporally, agricultural droughts across most regions of China displayed stable or alleviating trends, with particularly notable relief observed in Region VI. Spatially, 58.25 % of China's territory experienced a decrease in drought intensity, especially in the Qinghai-Tibetan Plateau, North China Plain, and southern regions, while certain areas in northern and southwestern China recorded an intensification of drought conditions. (4) The correlation between meteorological drought and agricultural drought was found to be stronger during the summer (R = 0.68) and autumn (R = 0.63) compared to winter and spring. The propagation time from meteorological drought to agricultural drought varied seasonally, being shortest in summer (2.54 months) and longest in winter (6.54 months). These findings highlight the potential of the Merged-SM dataset for improving agricultural drought monitoring and provide critical insights into the spatiotemporal dynamics and propagation mechanisms of droughts in China.